Draft Genome Sequence of Bacillus amyloliquefaciens B-1895 - Karlyshev, Andrey V. (American Society for Microbiology, 2014)
In this report, we present a draft genome sequence of Bacillus amyloliquefaciens strain B-1895. Comparison with the genome of a reference strain demonstrated similar overall organization, as well as differences involving large gene clusters.